PENGARUH KOMUNIKASI, SELF ESTEEM, DAN SELF EFFICACY TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA PERAWAT RUMAH SAKIT TGK. FAKINAH BANDA ACEH - Iska Maulina (Jurnal Manajemen Inovasi, 2017)
ABSTRACTThis study aimed to test on the Influence Communication, self esteem and self efficacy on job satisfaction of nurses and their impact on the performance of nurses Tgk. Fakinah Banda Aceh. Data retrieved by using census method with the number of respondents were 106 nurses who work in hospitals Tgk. Fakinah Banda Aceh. Primary data collection is done by distributing a questionnaire compiled using Likert scale and subsequently analyzed by using multiple linear regression analysis and hierarchical regression techniques to test the indirect effect among variables. The results showed that the communication variables proved to have no significant effect on job satisfaction and performance of hospital nurses Tgk.Fakinah Banda Aceh. This means that there are no variable role of communication in improving job satisfaction and performance of nurses in hospitals Tgk.fakinah Banda Aceh. Based on regression analysis, Self esteem has a positive and significant relationship with job satisfaction and there is a positive and significant influence to the performance of nurses. Self efficacy variable was also shown to have a positive and significant relationship with job satisfaction. This means that the stronger the self-efficacy was influential applied to increasing job satisfaction in hospitals Tgk. Fakinah Banda Aceh. However, when associated with the performance of the nurse, the analysis results showed that there was no positive influence and significant correlation between self efficacy and nurse's performance This means that the use of self-efficacy did not bring a positive impact on the performance of nurses Hospital Tgk. Fakinah Banda Aceh. Furthermore, job satisfaction variables have positive and significant correlation with the performance of nurses and no effect relationship is not direct (indirect effect) of a communication link with the performance of nurses mediated by job satisfaction. From the analysis of proving a direct link was found that there are significant indirect partial (partially mediation) on the relationship between self-esteem and performance of nurses mediated by job satisfaction. That is, the effect of self-efficacy on the performance of nurses will occur only if there is an increase in employee satisfaction at the Hospital of Tgk. Fakinah Banda Aceh.Keywords: Communication, Self Esteem and Self Efficacy, Job Satisfaction and Performance